Regulation of body weight: Lessons learned from bariatric surgery - Vance L. Albaugh; Yanlin He; Heike Münzberg; Christopher D. Morrison; Sangho Yu; Hans-Rudolf Berthoud (Elsevier, 2023)
Background: Bariatric or weight loss surgery is currently the most effective treatment for obesity and metabolic disease. Unlike dieting and pharmacology, its beneficial effects are sustained over decades in most patients, and mortality is among the lowest for major surgery. Because there are not nearly enough surgeons to implement bariatric surgery on a global scale, intensive research efforts have begun to identify its mechanisms of action on a molecular level in order to replace surgery with targeted behavioral or pharmacological treatments. To date, however, there is no consensus as to the critical mechanisms involved. Scope of review: The purpose of this non-systematic review is to evaluate the existing evidence for specific molecular and inter-organ signaling pathways that play major roles in bariatric surgery-induced weight loss and metabolic benefits, with a focus on Roux-en-Y gastric bypass (RYGB) and vertical sleeve gastrectomy (VSG), in both humans and rodents. Major conclusions: Gut-brain communication and its brain targets of food intake control and energy balance regulation are complex and redundant. Although the relatively young science of bariatric surgery has generated a number of hypotheses, no clear and unique mechanism has yet emerged. It seems increasingly likely that the broad physiological and behavioral effects produced by bariatric surgery do not involve a single mechanism, but rather multiple signaling pathways. Besides a need to improve and better validate surgeries in animals, advanced techniques, including inducible, tissue-specific knockout models, and the use of humanized physiological traits will be necessary. State-of-the-art genetically-guided neural identification techniques should be used to more selectively manipulate function-specific pathways.